Comparison of in vivo effects of insulin on SREBP‐1c activation and INSIG‐1/2 in rat liver and human and rat adipose tissue. (26th July 2013) - Boden, Guenther; Salehi, Sajad; Cheung, Peter; Homko, Carol; Song, Weiwei; Loveland‐Jones, Catherine; Jayarajan, Senthil
Abstract : Objective: The stimulatory effects of insulin on de novo lipogenesis (DNL) in the liver, where it is an important contributor to non‐alcoholic fatty liver disease (NAFLD), hepatic and systemic insulin resistance, is strong and well established. In contrast, insulin plays only a minor role in DNL in adipose tissue. The reason why insulin stimulates DNL more in liver than in fat is not known but may be due to differential regulation of the transcription and post‐translational activation of sterol regulatory element binding proteins (SREBPs). To test this hypothesis, we have examined effects of insulin on activation of SREBP‐1c in liver of rats and in adipose tissue of rats and human subjects. Design and Methods: Liver and epidydimal fat were obtained from alert rats and subcutaneous adipose tissue from human subjects in response to 4 h euglycemic‐hyperinsulinemic clamps. Results: Here we show that acutely raising plasma insulin levels in rats and humans increased SREBP‐1 mRNA comparably 3‐4 fold in rat liver and rat and human adipose tissue, but increased post‐translational activation of SREBP‐1c only in rat liver, while decreasing it in adipose tissue. These differential effects of insulin on SREBP‐1c activation in liver and adipose tissue were associated with robust changes in the opposite direction of INSIG‐1 and to a lesser extent of INSIG‐2 mRNA and proteins. Conclusions: We conclude that these findings support the hypothesis that insulin stimulated activation of SREBP‐1c in the liver, at least in part, by suppressing INSIG‐1 and ‐2, whereas in adipose tissue, an increase in INSIG‐1 and ‐2 prevented SREBP‐1c activation.